Empowerment Initiatives for Truno Djoyo Fish Farming Groups Through the Utilization of Bycatch Fishery in Wonorejo Village, Surabaya City - Putra, Oki Nugraha (SMONAGENES Research Center, Univeritas Brawijaya, 2026)
Tilapia and mullet have not been properly handled in Wonorejo Village, Rungkut District, Surabaya City. One potential strategy to increase its market value is to process it into salted fish products. This initiative aims to provide guidance, education, and training for fish pond farmer groups on producing salted fish free from hazardous chemicals, obtaining Home Industry Food Production permits, and utilizing digital marketing through e-commerce platforms. Through these efforts, participants are expected to produce, register, and market salted fish products independently. This initiative adopts an Asset-Based Community Development and Participatory Action Research approach. In addition to salt, the production process incorporates waru leaf extract as a natural preservative to extend shelf life. The service team also assisted in designing product labels that comply with permit registration requirements and provided drying ovens to help maintain product quality. The training results demonstrated a significant improvement in participants' knowledge of product diversification and managerial aspects, as evidenced by a paired t-test. In addition, this initiative strengthens partner empowerment in both production and management through productive business activities, increased income from salted fish sales, improved capacity for independent digital marketing, and enhanced legal compliance through assistance in obtaining home industry production permits. Collectively, these outcomes provide a foundation for gradual scaling up. The initiative has led to increased production capacity, stronger legal compliance through business permit facilitation, and improved digital marketing capabilities via e-commerce platforms. Therefore, continued support is essential to sustain these digital marketing efforts.